Business model and feasibility analysis for energy production as a self-producer by lease (Research, Society and Development, 2022)
The Electric Sector in Brazil is currently based on the presence of two markets for contracting energy. One available for access to all consumers only in the concession format, with contractual freedom and exclusive access by the government contracted for media consumption. These are respectively the Regulated Contracting Environment (ACR) and the Free Contracting Environment (ACL). In this last agent, among the other energy generators, the self-producer agent is defined, which has the right to generate energy for its own consumption. This configuration opens possibilities for media consumers, if the project is not regulated by a project that is not compatible with the market. Being a promising model, but recent in the market, it is necessary to define its general aspects, such as the aptitudes and costs of the enterprise, as well as to validate the economic viability of the model and its potential to reduce electricity costs. For this, applied research and a study of the Fluminense case will be presented, based on the values of the Federal University from a base and comparing them with market values for the new model. This article briefly presents aspects of the structuring of the Brazilian electricity sector, as well as the characteristics and differences of each contractual environment, such as the instruments of each market and its commercialization rules, in addition to the business model of self-production of energy of photovoltaic origin by asset leasing developed for Universidade Federal Fluminense to reduce electricity costs.